Obesity, overweight and breast cancer: new clinical data and implications for practice - García-Estévez, Laura; González-Rodríguez, Marta; Calvo, Isabel; Orta, Alberto; Gión, María; Moreno-Bueno, Gema; Pérez-García, José Manuel; Cortés, Javier (Frontiers in Oncology, 2025)
Excess bodyweight has negative consequences in breast cancer (BC) patients, significantly increasing the incidence of BC and adversely affecting clinical outcomes in most BC subtypes. This article overviews recent evidence relating to excess bodyweight (particularly obesity) and its effect on treatment in women with BC, focusing on latest evidence, including clinical findings from recently introduced new therapeutic entities. There is evidence of an inverse relationship between obesity and BC in premenopausal women highlighting a complex interplay involving the tumor microenvironment and tumor cells, and patient factors such as hormonal/metabolic/inflammatory status. Advancements in targeted- and immune-therapy have brought renewed optimism for women with BC. Ultimately, a better understanding of the mechanistic link between adipogenicity and tumorigenicity in breast tissues, as well as how obesity and adipose tissue inflammation interact with female sex hormones, may prove to be an important area for further refinements in our quest to develop a truly personalized therapeutic approach in this clinical setting.